PENGARUH KEMAMPUAN LITERASI DIGITAL DAN KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR MAHASISWA - Indah Susanty; Marsofiyati, Marsofiyati (Cahaya Ilmu Bangsa Institute, 2024)
This study aims to analyze the effect of digital literacy and learning independence on student learning outcomes in the Office Administration Education Study Program in 2022, Faculty of Economics, State University of Jakarta. This research is motivated by the importance of these two factors in determining student learning outcomes. Using a quantitative approach with a descriptive associative method, data were collected through distributing questionnaires to 45 students as respondents, which were then analyzed using SPSS. The results showed that digital literacy has no significant effect on student learning outcomes, with a t value of 0.792 and p = 0.433. In contrast, learning independence has a positive and significant effect on student learning outcomes, with a t value of 7.267 and p < 0.001. The F-test shows that both independent variables simultaneously have a significant effect on student learning outcomes (F-count = 47.949, p < 0.001). This finding implies that although digital literacy does not have a significant effect, learning independence has a greater contribution in improving student learning outcomes. This research is expected to provide insights for educators in designing more effective learning strategies with a focus on increasing student learning independence.